Proposing Innovative Genetic Algorithms Model to Solve the Problem of the Professors' Educational Planning Considering Students' Opinions - Laleh Asgari; mohammad reza keyvanpour (Nashrīyah-i mudīrīyat-i fannāvarī-i iṭṭilāʻāt, 2017)
Timing of curriculum planning for students and faculty could be done using diverse methods. The present research concerns with curriculum planning for professors considering the students' opinions. In doing so, the courses and the timing are determined based on the professors' common timetable, the professors' intensive courses timing and the class limitations. To achieve this goal, the genetic algorithm methodology was used in two steps. In the first stage, single-point cutting operator was used and in the second stage of the algorithm, a new intelligent operator called cyclic reverse list (RIL) was used provided that gold, silver and bronze time types were used for different courses. The advantages of this algorithm are using a new appropriate function (hot rolled), as well as new criteria and a new operator (RIL). Unlike conventional methods, in this method the appropriateness is considered in proportion with the whole population and we try to remove the impossible solutions. The optimal solution is chosen from among a multitude of provided responses. Therefore, it was found that we can reach the optimal solutions with regard to a better appropriateness.